(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
We consider the problem of detecting cardiac artery occlusions using stenosis driven viscoelastic (VE) waves propagated through biotissue to body surface sensors. We investigate possible statistical model formulations (ordinary least squares (OLS), generalized least squares (GLS)) and post analysis techniques (residual plots) to ascertain uncertainty in estimates as well as validity of the statistical models as part of a methodology for stenosis detection using viscoelastic waves.